Radio Frequency Identification and Telegram for Student Attendance - Kurniawan, Bobi; Fitriadi, L H; Albaroky, M F; Astiani, R (Universitas Komputer Indonesia, 2024)
The research aims at building a system that can record data attendance and Telegram notification utilizes Radio Frequency Identification (RFID) and Telegram. The research method used the experimental method to check the success time to retrieve the data. The results show that with 60 cards, the system can retrieve data in 3 minutes, 33 seconds, or 213 seconds without stopping. The system can see student attendance recaps stored in the database and notify when students come to school via Telegram to the parents of the respective students and class teachers. Reading the cards is also quite beneficial, so it prevents queues in attendance and makes it easier for officers to recap attendance